Linoleic acid: have we understood how it works in psychopathologies and Ischemic Cardiovascular Diseases? - Cocchi, Massimo; Mondo, Elisabetta; Minuto, Chara; Lercker, Giovanni (Progress in Nutrition, 2020)
The question about Linoleic Acid, which remains arguable, is whether the Linoleic Acid is inverselycorrelated to the Cardiovascular Disease or not and whether increasing the intake over the RecommendedDaily Allowance (RDA) is positive or negative. The scientific literature, past and recent, is stillcontroversial about the matter. To try to answer this controversy, it is important to remember the role of theLinoleic Acid in the membrane and its relationship with cholesterol. Furthermore, it is important to examinethe effect of the oxidation of Linoleic Acid, its impact on the gut microbiota and the consequences on the gutepithelial integrity.Highlights. Nutritional considerations about Linoleic Acid > Characteristic of oxidizability of Linoleic Acidwith respect to the cell membrane function > Linoleic Acid in platelets > The position of Linoleic Acid withrespect to Psychopathology and Ischemic Cardiovascular Disease > Linoleic Acid and its effect on gut bacteriaadhesion to gut epithelial barrier.